TIME-DEPENDENT HYDRAULIC RESISTANCE OF THE SOIL CRUST: HENRY'S LAW - Kutlek M. (My University, 2003)
In earlier experiments on steady infiltration into crust-topped soil columns an additional resistance was observed in the vicinity of the boundary between the crust and the soil below it. I have performed laboratory tests in order to check the following hypothesis: high hydraulic resistance of the crust results in steep drop of the water pressure between the top and bottom part of the crust if water flows through the crust-topped soil. The concentration of dissolved air in water depends upon the pressure acting on water according to linear Henry's law. I am assuming that air is released in small, microscopic air bubbles at the bottom part of the crust due to a substantial drop of the pressure. The microbubbles are then blocking a part of micropores of the crust. Consequently, hydraulic resistance of the crust increases. In laboratory experiments, the crust-topped soil was modeled by ceramic plate of high resistance placed on the top of the sand, or alternatively of loamy loess columns. Unsteady infiltration into crust-topped soil was repeatedly realized with Dirichlet's boundary condition and the plate resistance was measured at each selected time of infiltration. Flow in the whole system saturated by water was performed and resistance of the system was measured, too. Hydraulic resistance of the plate was rising with time during infiltration. The increase of hydraulic resistance was more expressed when water infiltrated into crust-topped initially dry sand than in experiments with sand of initially high water content. Resistance increasing with time was measured in nearly saturated systems, too. The hypothesis was therefore macroscopically proved.
Keywords: INFILTRATION; SOIL CRUST; LAYERED SOIL; HYDRAULIC RESISTANCE; HENRY'S LAW